2010
DOI: 10.1093/bjsw/bcq119
|View full text |Cite
|
Sign up to set email alerts
|

Child Protection and Safeguarding in England: Changing and Competing Conceptions of Risk and their Implications for Social Work

Abstract: This paper critically reflects on policy developments and debates in England in relation to child protection and safeguarding over the past twenty years. It argues that the period from the early 1990s to late 2008 saw policy change in significant ways. The state developed a much broader focus of concern about what constituted risk to children and what the role of professionals should be in relation to this; increasingy the emphasis was upon 'safeguarding' rather than 'child protection'. However, the period sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 28 publications
2
98
0
Order By: Relevance
“…Students tended to make judgments on the vignettes presented based on one orientation or the other. The notion of 'a child at risk' reflects a strong child protection orientation whilst 'a risk to the child' reflects a broader 'child welfare' orientation involving prevention and the provision of supportive services (Parton 2011). The findings suggested that students vacillate between different orientations reflecting the earlier noted nuanced approaches in international child welfare systems identified by Gilbert et al (2011).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Students tended to make judgments on the vignettes presented based on one orientation or the other. The notion of 'a child at risk' reflects a strong child protection orientation whilst 'a risk to the child' reflects a broader 'child welfare' orientation involving prevention and the provision of supportive services (Parton 2011). The findings suggested that students vacillate between different orientations reflecting the earlier noted nuanced approaches in international child welfare systems identified by Gilbert et al (2011).…”
Section: Discussionmentioning
confidence: 86%
“…Parton (2011) has identified that, in the 1970s and 1980s, in response to a series of high profile cases and associated criticism of social work, services in the UK, North America and Australia became dominated by concerns about risk. This child protection focus widened to some extent in the 1990s and 2000s, reflected in the use of the term 'safeguarding' in policy and practice, although risk remains central.…”
Section: Risk In Social Work Education and Practicementioning
confidence: 99%
“…With engagement as an underpinning ethos it may also be the most effective method of assessing and managing risk, more effective than more confrontational approaches. There is an on-going false dichotomy between family support and child protection, the latter very much coming to the fore when things go wrong (Parton, 2011). The recovery approach, as a form of family support and engagement, may therefore offer a more effective means of protecting children, through its inherent focus on a whole family perspective, where risk is assessed and managed in a spirit of collaboration, empowerment, partnership and openness.…”
Section: Resultsmentioning
confidence: 99%
“…This in itself had emerged from increasing awareness of the need to enhance the status of social work as a 3 'I once knew a team where all the workers called the manager "mother" '…..Some reflections on supervision within an integrated leadership and management programme Social Work and Social Services Review article Revised May 28 th 2013 profession (Laming, 2009;Munro, 2010); and that it was social work team managers (rather than other professionals) who were faced with particularly complex safeguarding issues. The scapegoating of social workers which intensified during the Baby Peter affair (Parton, 2011) reinforced the need for social work managers to be confident in their own decision making and their management of staff. While these reports related specifically to children, the steering group felt that similar issues faced adults services managers who faced the added challenges of few qualified staff and responsibility for widely diverse service areas within one team.…”
Section: Philosophy and Principlesmentioning
confidence: 99%
“…The professional social workers autonomy on behalf of her clients was sacrosanct. This began to change as child deaths focused attention on the role of professionals and official agencies (Parton, 2011) amplified by intense and critical media interest. Social workers' power needed to be curbed through increased managerial controls (Dustin, 2007).…”
Section: The Importance Of Supervisionmentioning
confidence: 99%